COMPARISON OF ULTRASOUND-GUIDED ANKLE BLOCK VERSUS ANATOMICAL LANDMARK-GUIDED ANKLE BLOCK IN ANKLE AND FOOT SURGERY UNDER REGIONAL ANESTHESIA - NAZ, U; SULAIMAN, .; HAROON, M; HAQ, IU; SULTAN, A; FARID, K (Biological and Clinical Sciences Research Journal, 2024)
As more patients undergo foot and ankle surgery, regional anesthesia’s significance in postoperative treatment has grown. Anesthesiologists and pain specialists have adopted regional anesthesia in large numbers. Numerous techniques, such as nerve stimulation, anatomical markers, and ultrasonography, have blocked the saphenous nerve. Objective: The present study aimed to assess the traditional anatomic landmark-guided approaches in lower limb surgery performed under regional anesthesia with ultrasound-guided ankle blocks in surgical anesthetic methods. Method: This randomized control study is carried out at the hospital. A total of 60 participants with scheduled foot and ankle surgery were randomly divided into two study groups (each n=30): Ultrasound-guided ankle block (USG) and anatomical landmark-guided ankle block (ALG). Results: Recruited participants had a mean age of 50.2± 14.02, with 39 (65%) male and 21 ( 35%) female. A total of 49 patients (82%) were able to undergo anesthesia successfully, with 26 (86.60%) of those patients belonging to the USG block group and 23 (76.60%) of those patients belonging to the ALG block group undergoing anesthesia successfully (p-value = >0.999). Conclusion: The results of this research indicate that the success rates of the two procedures are statistically insignificantly different; however, the USG ankle block for surgical anesthesia performed under regional anesthetic had a greater success rate than the anatomic landmark-guided technique.